Differential insertion of the atrioventricular valves: measurement protocol to detect various congenital heart defects. (1st June 2014) - Adriaanse, B. M. E.; Schats, J.; Tromp, C. H. N.; Uittenbogaard, L. B.; Heymans, M. W.; van Vugt, J. M. G.; Haak, M. C.
ABSTRACT Objectives The objectives of this study were to develop reference values for the distance between the atrioventricular valves, called differential insertion of the atrioventricular valves (DIAVV), in normal fetuses using four‐dimensional ultrasound with spatio‐temporal image correlation and to explore if DIAVV measurement can differentiate between normal hearts and hearts with cardiac defects. Methods The DIAVV was analysed longitudinally following a measurement protocol in 74 fetuses between 15 and 36 weeks gestational age. The DIAVV was measured in an apical four‐chamber view of the heart in end‐diastole. Furthermore, the DIAVV was measured in 70 fetuses with cardiac defects. Results In total, 337 normal and 70 abnormal spatio‐temporal image correlation volumes were examined. Longitudinal regression analysis revealed a positive relationship of the DIAVV with gestational age and fetal biometry (p < 0.0001). The DIAVV of fetuses with double outlet right ventricle, truncus arteriosus, atrioventricular septal defects, Ebstein and tetralogy of Fallot all differed from normal fetuses (p < 0.05). Conclusion Measurement of the DIAVV is a promising tool; however, a well‐defined measurement protocol should be followed to accomplish the correct plane and exact moment in the cardiac cycle. This study presents new nomograms following this measurement protocol and reports an abnormal DIAVV in a wide spectrum of congenital heart disease. © 2014 John Wiley & Sons, Ltd.